R=-4x-9z+5z-9x+3x-8z

Simple and best practice solution for R=-4x-9z+5z-9x+3x-8z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for R=-4x-9z+5z-9x+3x-8z equation:


Simplifying
R = -4x + -9z + 5z + -9x + 3x + -8z

Reorder the terms:
R = -4x + -9x + 3x + -9z + 5z + -8z

Combine like terms: -4x + -9x = -13x
R = -13x + 3x + -9z + 5z + -8z

Combine like terms: -13x + 3x = -10x
R = -10x + -9z + 5z + -8z

Combine like terms: -9z + 5z = -4z
R = -10x + -4z + -8z

Combine like terms: -4z + -8z = -12z
R = -10x + -12z

Solving
R = -10x + -12z

Solving for variable 'R'.

Move all terms containing R to the left, all other terms to the right.

Simplifying
R = -10x + -12z

See similar equations:

| x*2=1/25 | | 9y^2+1=6x | | (10x^6)(5x^2)= | | A=-7x+3y-7y+8x-6x+9y | | 15x^2+x^3=0 | | 0.5x^3-1.5x^2+4=0 | | V=-9y+7y-5+4 | | x-150000=1.4x | | X=582 | | .006*x=12 | | 9x+1-9x=72 | | 2*ln^2(2)=x | | .2+6x=.8-7x | | .6*x=12 | | e+m= | | 15x^2-x^3=0 | | P=-8z-7z+8-5 | | 2x+4=4+5c | | X^3-12x=55 | | 2(x+2)=3x+1 | | .50*p=30 | | 2x^2/x-2 | | S=-6z+9z-7z | | 50*p=30 | | Q=-5y+4y | | Z^4+6z^2+25=0 | | 20n=8 | | 700+0.15x=750 | | 7V+2B=164 | | K=-5c-8c | | -4(3x-1)+2=-12x+6 | | 6y-14=26 |

Equations solver categories